Rate of Distribution of Breast Lump in Different Quadrants with Their Cytological Findings in Both Sex - Nahar, Nazmun; Iqbal, Mohammed; Rahman, Kazi Md Shahidur; Md Arif, Nazim Uddin; Rahman, Md Mizanur; Naheen, Towhida; Alam, Mohammed Safiul; Das, Soma (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: The breast lump is a localized swelling, protuberance, bulge, or bump in the breast that feels different from the breast tissue around it or the breast tissue in the same area of the other breast. Objective: The purpose of the present study was to find out the frequency of breast lump in different quadrants and their cytological findings. Methodology: The present study was carried out at the Department of Pathology, Chittagong Medical College, Bangladesh one-year period from May 2005 to June 2006. This study was cross sectional which included 110 cases of breast lump. The patients with breast lump were received from indoor and outdoor patient Department of Surgery, Chittagong Medical College, Bangladesh. The patient presents with definite palpable lump, irrespective of age and sex were included in this study. Result: This study shows only 1.8% male were found central quadrant individual breast. In female maximum (46.4%) were found in upper & outer quadrant individual breast. Right sided of affected breast in highest percentage of upper & outer quadrant individual breast (21.8%). Also shows left side of affected breast in highest percentage of upper & outer quadrant individual breast (24.5%). It was observed that maximum (34.5%) upper & outer quadrant individual breast was seen in benign lesion and (3.6%) were suspicious. But maximum (12.7%) were show multiple in malignant lesion. Conclusion: In conclusion highest frequency of patients are reported in upper outer quadrant breast lump followed by multiple, central, lower & inner and lower & outer. It also observed that the upper outer quadrant is the most commonly affected quadrant in benign and multiple quadrant the malignant breast neoplasms. Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 69-71